The Swedish motor neuron disease quality registry. Issue 7 (2nd October 2018) - Longinetti, Elisa; Regodón Wallin, Amanda; Samuelsson, Kristin; Press, Rayomand; Zachau, Anne; Ronnevi, Lars-Olof; Kierkegaard, Marie; Andersen, Peter M; Hillert, Jan; Fang, Fang; Ingre, Caroline
Abstract: Objective : We set up the Swedish Motor Neuron Disease (MND) Quality Registry to assure early diagnosis and high-quality health care for all MND patients (mainly amyotrophic lateral sclerosis, ALS), and to create a research base by prospectively following the entire MND population in Sweden. Methods : Since 2015, the MND Quality Registry continuously collects information about a wide range of clinical measures, biological samples, and quality of life outcomes from all MND patients recruited at the time of MND diagnosis in Sweden and followed at each clinic visit approximately every 12 weeks. The Registry includes an Internet based patient own reporting portal that involves patients in the registration of their current symptoms and health status. Results : As of 20th January 2017, the MND Quality Registry included 99% of the MND patients of the Stockholm area (N = 194), consisting mostly of ALS patients ( N = 153, 78.9%), followed by patients labeled as MND due to a neurophysiology finding but not fulfilling the criteria for ALS ( N = 20, 10.3%), primary lateral sclerosis ( N = 13, 6.7%), and progressive spinal muscular atrophy patients ( N = 8, 4.1%). A higher proportion of these patients were women ( N = 100, 52%), and women and men had a similar age at symptoms onset (59 years). Conclusions: Main strengths of the MND Quality Registry are its clinical, quantitative, qualitative, and prospective nature, providing the researchers potential means of identifying appropriate candidates for clinical trials and other research projects, as well as assuring to the patients an effective and adequate time spent on-site with the healthcare professionals.